Mobilisation of an international Urban Search and Rescue team - Fauré, J. L. (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2015)
Thesis (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2012.